The pious man and his son - Khan , Saniyasnain (India, Good word books, 1999)
The story centers on Prophet Ya'qub (Jacob) and his twelve sons, particularly focusing on the bond between Ya'qub and his son Yusuf (Joseph). The narrative explores themes of jealousy, patience, and faith. When Yusuf's brothers, envious of their father's affection for him, plot to harm him, Ya'qub's unwavering trust in Allah and his patience during the trials are highlighted. The story emphasizes the importance of maintaining faith and integrity in the face of adversity.